Clinical end pharmacoeconomic aspects of neoadjuvant therapy of breast cancer - V. A. Kostorov; T. Yu. Semiglazova; A. V. Pavlysh (Медицинский совет, 2018)
Achievement of complete Pathomorphologic Response (pCR) after neoadjuvant therapy of breast cancer significantly improves long-term treatment outcome. Correlation between pCR and long-term treatment outcome is strongest in HER2-positive breast cancer; this data clearly supports use of double HER2-blockade in neoadjuvant breast cancer therapy. However, the high cost of targeted drugs requires pharmacoecomomic assessments for choosing of the most optimal treatment course.